PENERAPAN MODEL PEMBELAJARAN PROJECT BASED LEARNING MENGGUNAKAN APLIKASI MAPLE CALCULATOR UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA - Taufiq Taufiq; Junaidi Junaidi; Mirunnisa Mirunnisa; Suci Maulina; Selfina Selfina (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2025)
This study aims to improve the critical thinking skills of students of SMA Negeri 1 Sigli through the application of the Project Based Learning learning model using the maple calculator application. The population in this study were all 210 students of grade XI of SMA Negeri 1 Sigli. The population in this study was more than 100, so a sample of 2 (two) classes was taken, namely the experimental class and the control class, totaling 60 students. The research method used was quasi-experimental. The experimental class used the Project Based Learning model using the maple calculator application, while the control class was given learning with conventional methods. Data collection was carried out with a final test, and data processing used the t-test. The results of data analysis showed that the average value of the experimental class was higher, namely 87.40 and the control class 79.27. The results of hypothesis testing obtained t-count t-table, namely 3,541 2,002. Thus, the application of the Project-Based Learning learning model using the maple calculator application can improve the critical thinking skills of students of SMA Negeri 1 Sigli.